ANALYSIS OF THE SUITABILITY OF SCIENCE TEXTBOOKS SMP GRADE VII (POLLUTED WATER THEME) WITH INDICATORS OF CRITICAL THINKING ABILITY - Rizkiyati Puteri Utami; Suroso Mukti Leksono; Annisa Novianti Taufik (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
This study aimed to analyze the emergence of indicators critical thingking skills in the 7th grade junior high school science learning textbook on the theme of polluted water. The indicators of critical thingking skills that analyzed are focusing on question, analyzing arguments, asking and answering questions, considering whether the source is reliable or not, observing and considering an observation, making deductions and considering, the results of deductions, making inductions and considering the results of induction, making and considering decisions value, define terms and consider definitions, identify assumptions, define an action and interact with others. This research was a descriptive study by using document analysis method to describe the emergence of indicators critical thingking skills in each sub-material component in the science learning textbook. The object of this research was the science leaning textbook published by Kemendikbud, Erlangga and Quadra. The data collection technique used documentation. The instrument used a checklist sheet. Analysis of research data used descriptive statistics by calculating the number of components of the analysis in accordance with the indicators of critical thingking skills. The results of the analysis of the emergence of indicators critical thingking indicators in the three science learning textbooks that were analyzed, the emergence of indicators critical thingking skills obtained the highest percentage in the kemendikbud book of 83,33% very good. Meanwhile, Erlangga’s book was 66,67% good and Quadra 56,68% good enough.